PENINGKATAN MOTIVASI DAN HASIL BELAJAR MAHASISWA MELALUI PENERAPAN STRATEGI PEMBELAJARAN INKUIRI - Novrianti Novrianti (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2014)
The aim of the research was to know the effect of the implementation of an inquiry learning strategy in increasing students’ learning motivation and achivement. The research is classified into a classroom action research. The research was conducted in the teaching of Program Evaluation subject at Educational Technology Study Program. The subject of the research was the seventh semester students. The research was conducted in three circles. Each circle consisted of four steps: planning, implementation, observation, and reflection. The data were collected through observation, questionnaire, and test. The data were analyzed descriptively and statistically. The findings of the research showed that the use of inquiry learning strategy increased students’ learning motivation in the teaching of Evaluation Program subject. The increase of students’ motivation was observed individually and classically. With high learning motivation, in the long run, it is predicted that students’ learning achievement would also increase.